2010
DOI: 10.1007/s11671-010-9793-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanospiral Formation by Droplet Drying: One Molecule at a Time

Abstract: We have created nanospirals by self-assembly during droplet evaporation. The nanospirals, 60–70 nm in diameter, formed when solvent mixtures of methanol and m-cresol were used. In contrast, spin coating using only methanol as the solvent produced epitaxial films of stripe nanopatterns and using only m-cresol disordered structure. Due to the disparity in vapor pressure between the two solvents, droplets of m-cresol solution remaining on the substrate serve as templates for the self-assembly of carboxylic acid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Therefore, the limiting inner/outer diameter should be related to the limiting intermolecular interactions. We presume a similar scenario for the previously reported molecular rings/spirals. , Thus, it is summarized that molecular rings formed by predominantly weak intermolecular interactions should always possess a limiting inner/outer diameter and should be independent of size, shape, and chemical nature of the molecules. We also note that the molecular rings with a very small inner diameter (∼4 nm) are possible if the formation of rings is assisted by a strong molecule–substrate interaction. , …”
supporting
confidence: 82%
See 2 more Smart Citations
“…Therefore, the limiting inner/outer diameter should be related to the limiting intermolecular interactions. We presume a similar scenario for the previously reported molecular rings/spirals. , Thus, it is summarized that molecular rings formed by predominantly weak intermolecular interactions should always possess a limiting inner/outer diameter and should be independent of size, shape, and chemical nature of the molecules. We also note that the molecular rings with a very small inner diameter (∼4 nm) are possible if the formation of rings is assisted by a strong molecule–substrate interaction. , …”
supporting
confidence: 82%
“…We also find a surprising correlation in the inner/outer limiting diameters of the molecular rings of FcS 2 C 4 and FcS 2 C 3 with those of a few reported molecules. , See the comparison in the table provided in the SI. The biggest surprise here is whether the correlation is a mere coincidence or it suggests that the inner/outer diameter of molecular rings is independent of the molecular geometry and size.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Over the past decades scientific provisions on drying have been continuously developed. A large number of mathematical models have been published for various drying methods, most of which are based either on a system of differential interrelated equations of mass and energy transfer [6,13], or on statistical processing of experimental research data for a specific product [3,7,8,9,10,11,12]. Sufficient information about the main directions of this development can be found at some practical conferences [6].…”
Section: Analytical Reviewmentioning
confidence: 99%
“…For example, Liu and co-workers described the formation of spirals of a barbituric acid derivative at the air/water interface, 4 whereas Wan et al demonstrated the formation of similar spiral like superstructures upon controlled evaporation of a specific solvent mixture containing saturated fatty acids. 5 We have studied the assembly of monolayers and multilayers of molecules which contain tetrathiafulvalenes (TTFs) and have shown that depending on the number and position of amide groups which assist in the intermolecular attraction various fibre-like morphologies are obtained. 6 One of these compounds (1), the object of this study, forms physisorbed multilayers at the interface between graphite and octanoic acid in a dynamic system where the liquid is still present.…”
mentioning
confidence: 99%